PERENCANAAN KEARSIPAN KANADA: PEMBELAJARAN BAGI PENYELENGGARAAN KEARSIPAN DI INDONESIA: Array - Sari Hasanah (Jurnal Kearsipan, 2017)
Planning is very important because it brings the future into present. In the absence of a good planning, it will be difficult to achieve the vision since all stakeholders work individually with different goals. Today, the archives in Indonesia do not have a planning document that unites all stakeholders and can be used as a national reference in achieving the vision. This study discusses on the Canadian Archival Planning which spans a period of ten years from 2016-2026. The approach in this study is a qualitative method. The determination of vision, strategy and steps to achieve the vision is clearly explained in this Canadian archival planning document so that the archives institutions in Indonesia can learn lessons from this. The strategies of the Canadian archival community have four areas of focus: the records, the people, the capacity and the profile. This research recommends that a working team should be formed in preparing long-term archival planning documents, and it needs the involvement from all stakeholders of the archives. Archival community in Indonesia needs to discuss and should has a commitment to implement strategies in achieving the vision.